Productivity and economics of maize–squash intercropping at different planting systems (Journal of the Bangladesh Agricultural University, 2018)
The competitive behaviors of maize–squash intercropping at different planting systems were studied at Regional Agricultural Research Station, Hathazari, Chittagong, Bangladesh during the Rabi season of 2016–17 to find out the suitable planting arrangement of maize–squash intercropping for maximum productivity and economic return. There were seven treatments i.e. T1= sole maize, T2= 1 row maize (100%) + 1 row squash (6 plants/row), T3= maize paired row (100%) + 1 row squash (5 plants/row), T4= maize paired row (100%) + 1 row squash (4 plants/row), T5= maize paired row (100%) + 2 row squash (5 plants/row), T6= maize paired row (100%) + 2 row squash (4 plants/row) and T7= sole squash. Results revealed that the Maize Equivalent Yield (MEY) was highest (18.39 t/ha) in T5treatment, where Maize paired row (100%) + 2 row squash (5 plants/row) was consummated. The highest Land Equivalent Ratio (LER) 1.62 was found in T5 treatment. Benefit-Cost Ratio (BCR) was also the highest (3.29) in T5 treatment. Maize paired row (100%) and two rows of squash (5 plants /row) was the suitable row arrangement of the intercrops for judicious use of land consisting optimum populations of the component crops to produce more yield and economic profitJ. Bangladesh Agril. Univ. 16(1): 23-26, April 2018